LEGAL CERTAINTY ANALYSIS IN THE EXTENSION OF LAND RIGHTS BASED ON THE AGRARIAN LAW - Salmon Sihite; Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyse legal certainty in the extension of land rights based on the Basic Agrarian Law (UUPA). The research method used is a literature review, examining various laws and regulations, scientific literature, and court decisions related to the extension of land rights. The analysis reveals that the UUPA has established a clear legal framework to provide protection and legal certainty for rights holders such as the Right to Use for Business (HGU), the Right to Build (HGB), and the Right to Use. However, implementation in the field still faces a number of challenges, such as the complexity of administrative procedures, overlapping land data, and coordination issues between institutions, which have the potential to cause legal uncertainty and disputes. Therefore, it is necessary to strengthen regulations, modernise the land administration system, and enhance public literacy to ensure that legal certainty regarding the extension of land rights can be achieved optimally in accordance with the provisions of the UUPA.